The stigma of mental illness in society and its effect on the search for psychological help - Mubarok, Ahmad Shofi (Jurnal Psikologi dan Konseling West Science, 2025)
This study investigates the stigma surrounding mental disorders in Indonesian society and its impact on individuals’ willingness to seek psychological help. Using a quantitative approach, data were collected from 80 respondents through a structured questionnaire employing a 5-point Likert scale. The results, analyzed using SPSS version 25, revealed a significant negative correlation between stigma and help-seeking behavior, with stigma accounting for 29% of the variance in help-seeking attitudes. The findings emphasize stigma as a critical barrier to accessing mental health services in Indonesia, influenced by cultural and social norms. Strategies to reduce stigma through public education and culturally sensitive interventions are recommended to encourage help-seeking behavior and improve mental health outcomes.